Somatostatin and Its Receptors in Myocardial Ischemia/Reperfusion Injury and Cardioprotection - Vörös, Imre; Sághy, Éva; Pohóczky, Krisztina; Makkos, András; Onódi, Zsófia; Brenner, Gábor B.; Baranyai, Tamás; Ágg, Bence; Váradi, Barnabás; Kemény, Ágnes; Leszek, Przemyslaw; Görbe, Anikó; et al. (Frontiers in Pharmacology, 2021)
Little is known about the role of the neuropeptide somatostatin (SST) in myocardial ischemia/reperfusion injury and cardioprotection. Here we investigated the direct cardio-cytoprotective effect of SST in ischemia/reperfusion injury in cardiomyocyte cultures, as well as the expression of SST and its receptors in pig and human heart tissues. SST induced a bell-shaped, concentration-dependent cardio-cytoprotection both in adult rat primary cardiomyocytes and H9C2 cells subjected to simulated ischemia/reperfusion injury. Furthermore, in a translational porcine closed-chest acute myocardial infarction model, ischemic preconditioning increased plasma SST-like immunoreactivity. Interestingly, SST expression was detectable at the protein, but not at the mRNA level in the pig left ventricles. SSTR1 and SSTR2, but not the other SST receptors were detectable at the mRNA level by PCR and sequencing in the pig left ventricle. Moreover, remote ischemic conditioning upregulated SSTR1 mRNA. Similarly, SST expression was also detectable in healthy human interventricular septum samples at the protein level. Furthermore, SST-like immunoreactivity decreased in interventricular septum samples of patients with ischemic cardiomyopathy. SSTR1, SSTR2 and SSTR5 but not SST and the other SST receptors were detectable at the mRNA level by sequencing in healthy human left ventricles. In addition, in healthy human left ventricle samples, SSTR1 and SSTR2 mRNAs were expressed especially in vascular endothelial and some other cell types as detected by RNA Scope® in situ hybridization. This is the first demonstration that SST exerts a direct cardio-cytoprotective effect against simulated ischemia/reperfusion injury. Moreover, SST is expressed in the heart tissue at the peptide level, however, it is likely to be of sensory neural origin since its mRNA is not detectable. SSTR1 and SSTR2 might be involved in the cardioprotective action of SST, but other mechanisms cannot be excluded.